2015
DOI: 10.1155/2015/971217
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Rare Case of Vulvar Myxoid Epithelioid Sarcoma

Abstract: Epithelioid sarcoma is a distinct sarcoma type with specific morphology and immunophenotype. An epithelioid sarcoma of the vulva is an extremely rare and aggressive tumor and most commonly occurs on the labia majora in women of reproductive age. Only few cases have been reported, especially with the presence of focal myxoid changes. Early diagnosis is difficult because of its benign appearance as a painless subcutaneous nodule. Optimal treatment is not well established due to its rarity. We report a successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 19 publications
2
16
0
1
Order By: Relevance
“…Therefore, it can be diagnosed using IHC [ 6 ]. Our case showed high IHC positivity rates for CD34, CK-PAN, and VT, which is in agreement with the results of the previous studies in this series [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it can be diagnosed using IHC [ 6 ]. Our case showed high IHC positivity rates for CD34, CK-PAN, and VT, which is in agreement with the results of the previous studies in this series [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…Adjuvant radiotherapy is recommended for high-grade tumors or cases with inadequate surgical margins [ 13 ]. We did not perform chemotherapy for our case, in accordance with previous studies that showed that the treatment effects of postoperative chemotherapy are still controversial [ 7 , 11 - 14 ]. Argenta et al [ 13 ] performed adjuvant chemotherapy for 7 of 31 patients with vulva ES or malignant rhabdoid tumor and reported that of the 7 patients, 3 were disease-free at 8, 11, and 21 months but the remaining 4 died of disseminated disease within 8 months of diagnosis.…”
Section: Discussionmentioning
confidence: 53%
“…Vulvar cancer is the fourth most common cause of gynecological malignancy, constituting 5% of all cancers of the female genital tract [1,2] , Among the various histological types of vulvar cancer, squamous cell carcinoma is the most common type and represents 95% of all malignant neoplasms in this gynecological area, followed by melanoma, sarcoma, and basal cell carcinoma [1] . Primary vulvar sarcomas are rare, reaching an incidence of 1.5 to 5% of cancers in this topographic region [2,3] . Epithelioid sarcoma (ES) is a malignant soft tissue neoplasm of uncertain histogenesis, which was established as a distinctive disease by Ezinger in 1970 [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Vulvar sarcoma constitutes 1.5-5% of all malignancies in this gynecologic region [1][2][3][4][5] . Types of sarcomas commonly present in the vulva include leiomyosarcomas, malignant fibrous histiocytoma, malignant rhabdoid tumor, angiosarcoma, rhabdomyosarcoma, and epithelioid sarcomas [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation